Mucorales spores induce a proinflammatory cytokine response in human mononuclear phagocytes and harbor no rodlet hydrophobins. Issue 8 (17th November 2017) - Wurster, Sebastian; Thielen, Vanessa; Weis, Philipp; Walther, Paul; Elias, Johannes; Waaga-Gasser, Ana Maria; Dragan, Mariola; Dandekar, Thomas; Einsele, Hermann; Löffler, Jürgen; Ullmann, Andrew J.
ABSTRACT: Mucormycoses are life-threatening infections in immunocompromised patients. This study characterizes the response of human mononuclear cells to different Mucorales and Ascomycota. PBMC, monocytes, and monocyte derived dendritic cells (moDCs) from healthy donors were stimulated with resting and germinated stages of Mucorales and Ascomycota. Cytokine response and expression of activation markers were studied. Both inactivated germ tubes and resting spores of Rhizopus arrhizus and other human pathogenic Mucorales species significantly stimulated mRNA synthesis and secretion of proinflammatory cytokines. Moreover, R. arrhizus spores induced the upregulation of co-stimulatory molecules on moDCs and a specific T-helper cell response. Removal of rodlet hydrophobins by hydrofluoric acid treatment of A. fumigatus conidia resulted in enhanced immunogenicity, whereas the cytokine response of PBMCs to dormant R. arrhizus spores was not influenced by hydrofluoric acid. Scanning electron micrographs of Mucorales spores did not exhibit any morphological correlates of rodlet hydrophobins. Taken together, this study revealed striking differences in the response of human mononuclear cells to resting stages of Ascomycota and Mucorales, which may be explained by absence of an immunoprotective hydrophobin layer in Mucorales spores.